ST‐segment depression and left ventricular systolic function recovery post‐atrial fibrillation ablation in heart failure - Masamichi Yano; Yasuyuki Egami; Shodai Kawanami; Kohei Ukita; Akito Kawamura; Koji Yasumoto; Masaki Tsuda; Naotaka Okamoto; Yasuharu Matsunaga‐Lee; Masami Nishino (ESC Heart Failure, 2024)
Abstract Aims Catheter ablation (CA) of atrial fibrillation (AF) improves left ventricular ejection fraction (LVEF) in patients with heart failure with reduced ejection fraction (HFrEF). The impact of ST‐segment depression before CA on LVEF recovery and clinical outcomes remains unknown. In the present study, we aimed to investigate the relationship between ST‐segment depression during AF rhythm before CA and improvement in the LVEF and clinical outcomes in persistent atrial fibrillation (PerAF) patients with HFrEF. Methods and results The present study included 122 PerAF patients (male; 98 patients, 80%, mean age: 69 [56, 76] years) from the Osaka Rosai Atrial Fibrillation ablation (ORAF) registry who had LVEF < 50% and underwent an initial ablation. The patients who underwent percutaneous coronary intervention or coronary artery bypass grafting within the past 1 month were not included in the enrolled patients. We assigned the patients based on the presence of ST‐segment depression before CA during AF rhythm and evaluated improvement in the LVEF (LVEF ≥ 15%) 1 year after CA and the relationship between ST‐segment depression and heart failure (HF) hospitalization/major adverse cardiovascular events (MACE), which are defined as a composite of HF hospitalization, cardiovascular death, hospitalization due to coronary artery disease, ventricular arrhythmia requiring hospitalization and stroke. The percentage of patients with improvement in the LVEF 1 year after CA was significantly lower in the patients with ST‐segment depression than those without (58.6% vs. 79.7%, P = 0.012). Multiple regression analysis showed ST‐segment depression was independently and significantly associated with improvement in the LVEF 1 year after CA (HR: 0.35; 95% CI: 0.129–0.928, P = 0.035). Kaplan–Meier analysis showed that the patients with ST‐segment depression significantly had higher risk of HF hospitalization and MACE than those without (log rank P = 0.022 and log rank P = 0.002, respectively). Multivariable Cox proportional hazards analysis showed that ST‐segment depression was independently and significantly associated with a higher risk of MACE (HR: 2.82; 95% CI: 1.210–6.584, P = 0.016). Conclusions ST‐segment depression before CA during AF rhythm was useful prognostic predictor of improvement in the LVEF and clinical outcomes including HF hospitalization and MACE in PerAF patients with HFrEF.